Preparation and Fluorescence Behaviour of Violet Waterborne Polyurethane using Disperse Violet 28 as Extender - Hu, Xianhai; Liu, Jin; Li, Yu; Cao, Fengmin (Asian Journal of Chemistry, 2014)
A polymeric dye, waterborne polyurethane-based disperse violet 28 (WPU-DV28), was prepared by incorporation of disperse violet 28 (DV28) into waterborne polyurethane chains. The structure of waterborne polyurethane-based dye was confirmed by FT-IR and UV-visible spectra. This polymeric dye exhibited intriguing optical behaviour. WPU-DV28 latex engendered a new peaks at 490 nm with contrast to disperse violet 28 in UV-visible spectra. The fluorescence intensity of WPU-DV28 latex was dramatically enhanced with contrast to that of disperse violet 28, which was attributed to hindering the formation of exciplexes in the disperse violet 28 units and augmentation of light absorption area. Furthermore, the fluorescence of WPU-DV28 was not sensitive to hydroquinone quencher.